Comparable calcium handling of human iPSC-derived cardiomyocytes generated by multiple laboratories. (August 2015) - Hwang, Hyun Seok; Kryshtal, Dmytro O.; Feaster, T.K.; Sánchez-Freire, Verónica; Zhang, Jianhua; Kamp, Timothy J.; Hong, Charles C.; Wu, Joseph C.; Knollmann, Björn C.
Abstract: Cardiomyocytes (CMs) derived from human induced pluripotent stem cells (hiPSCs) are being increasingly used to model human heart diseases. hiPSC-CMs generated by earlier aggregation-based methods (i.e., embryoid body) often lack functional sarcoplasmic reticulum (SR) Ca stores characteristic of mature mammalian CMs. Newer monolayer-based cardiac differentiation methods (i.e., Matrigel sandwich or small molecule-based differentiation) produce hiPSC-CMs of high purity and yield, but their Ca handling has not been comprehensively investigated. Here, we studied Ca handling and cytosolic Ca buffering properties of hiPSC-CMs generated independently from multiple hiPSC lines at Stanford University, Vanderbilt University and University of Wisconsin-Madison. hiPSC-CMs were cryopreserved at each university. Frozen aliquots were shipped, recovered from cryopreservation, plated at low density and compared 3–5 days after plating with acutely-isolated adult rabbit and mouse ventricular CMs. Although hiPSC-CM cell volume was significantly smaller, cell capacitance to cell volume ratio and cytoplasmic Ca buffering were not different from rabbit-CMs. hiPSC-CMs from all three laboratories exhibited robust L-type Ca currents, twitch Ca transients and caffeine-releasable SR Ca stores comparable to adult CMs. Ca transport by sarcoendoplasmic reticulum Ca ATPase (SERCA) and Na/Ca exchanger (NCX) was similar in all hiPSC-CM lines, but slower compared to rabbit-CMs. However, the relative contribution of SERCA and NCX to Ca transport of hiPSC-CMs was comparable to rabbit-CMs. Ca handling maturity of hiPSC-CMs increased from 15 to 21 days post-induction. We conclude that hiPSC-CMs generated independently from multiple iPSC lines using monolayer-based methods can be reproducibly recovered from cryopreservation and exhibit comparable and functional SR Ca handling. Highlights: We studied Ca handling and cytosolic Ca buffering properties of hiPSC-CMs from multiple hiPSC lines. Ca fluxes of hiPSC-CMs with primary rabbit and mouse-CMs. Independently generated hiPSC-CM lines have comparable and reproducible Ca handling and buffering